The efficacy of fractional carbon dioxide (CO2) laser combined with luliconazole 1% cream for the treatment of onychomycosis: A randomized, controlled trial. Issue 44 (November 2016) - Zhou, Bing Rong; LU, Yan; Permatasari, Felicia; Huang, He; Li, Jin; Liu, Juan; Zhang, Jia An; Luo, Dan; Xu, Yang
Abstract: Background: To evaluate the efficacy of fractional carbon dioxide (CO2 ) laser combined with luliconazole 1% cream for the treatment of onychomycosis and to compare it with that of fractional CO2 laser alone. Methods: This was a randomized, parallel group, 2-arm, positive-controlled, single-center, superiority trial with a 1:2 allocation ratio. Sixty patients with clinical and mycological diagnosis of onychomycosis were enrolled from the Dermatology Department of the First Affiliated Hospital of Nanjing Medical University in Nanjing, China from March 2015 to May 2015. Patients were randomized following simple randomization procedures (computerized random number generator) into 2 groups; L group only received 12 sessions of laser treatment at 2-week interval for 6 months, while L + D group received 12 sessions of laser treatment at 2-week interval combined with luliconazole 1% cream once daily for 6 months. This was not a blind trial. The main outcome measures were the clinical efficacy rate (CER) assessed from the percentage of fully and >60% normal-appearing nails and the mycological clearance rate (MCR) assessed from the percentage of nails with negative fungal microscopy. There were no changes to trial outcome measures after the trial commenced. Results: A total of 60 patients (N = 233 nails) completed treatments and follow-up, and were randomized and divided into 2 groups: L group (31 patients, N = 108 nails) and L + D group (29 patients, N = 115 nails). The CER and MCR of L + D group were 69.6% and 57.4%, respectively. L + D group showed significantly higher CER (69.6% vs 50.9%; χ 2 = 8.1, P = 0.004) and MCR (57.4% vs 38.9%; χ 2 = 7.6, P = 0.006) compared with those in L group. Some patients experienced mild pain during laser treatment, but there was no bleeding or oozing during or after treatment. There were no adverse effects reported during the observation period. Conclusion: Fractional CO2 laser treatment combined with 1% luliconazole cream for 6 months was an effective and safe method for the treatment of onychomycosis, and had a higher efficacy than fractional CO2 laser treatment alone.